Cognitive deficits early in the course of rheumatoid arthritis. Issue 7 (8th August 2016) - Simos, Panagiotis; Ktistaki, Georgia; Dimitraki, Georgia; Papastefanakis, Emmanouil; Kougkas, Nikolaos; Fanouriakis, Antonios; Gergianaki, Irini; Bertsias, George; Sidiropoulos, Prodromos; Karademas, Evangelos C.
ABSTRACT: Objective : The aim was to examine the severity and prevalence of cognitive difficulties in persons with rheumatoid arthritis (RA) within the first three years of diagnosis. Method : One hundred consecutive RA patients aged 28–67 years (90% women) were administered a battery of 6 neuropsychological tests yielding 14 cognitive indices. Self-reported measures of trait anxiety, depression, impact of disease on daily activities, and pain severity were also obtained along with physician-rated disease severity. Results : Twenty percent of RA patients were classified as cognitively impaired, defined as age- and education-adjusted scores at least 1.5 standard deviations below the population mean on 3 or more cognitive indices. Impaired performance, controlling for age, education, and premorbid cognitive capacity, was detected primarily on measures of short-term memory, immediate and delayed episodic recall, and phonemic fluency. There were modest negative associations between cognitive indices and measures of perceived disease severity (pain level, impact of disease on daily functionality, and overall health quality). Conclusions : Cognitive deficits on several domains are frequently encountered in relatively young RA patients during the first few years of the disease and may need to be taken into account as important correlates of disease severity and progression.